2020
DOI: 10.3390/d12090333
|View full text |Cite
|
Sign up to set email alerts
|

Are the Neglected Tipuloidea Crane Flies (Diptera) an Important Component for Subterranean Environments?

Abstract: Usually, biospeleological studies focus on cave-specialist taxa showing strong adaptation to the subterranean environment, as their unusual morphological and ecological features represent intriguing case studies. On the other hand, species occurring in subterranean environments but without marked adaptations have been generally overlooked, probably because they are thought to be accidental and not very important for the ecosystem. Particularly exemplificative is the case of Tipuloidea crane flies (Diptera), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…With this study we were able to gather only limited information on the diet of Speleomantes hybrids. Most of the prey consumed were Diptera, which can be highly abundant near the entrance of subterranean environments, especially during the hot season [28,29]. This is in agreement with previous studies on the Speleomantes diet [16,30,31].…”
Section: Discussionsupporting
confidence: 92%
“…With this study we were able to gather only limited information on the diet of Speleomantes hybrids. Most of the prey consumed were Diptera, which can be highly abundant near the entrance of subterranean environments, especially during the hot season [28,29]. This is in agreement with previous studies on the Speleomantes diet [16,30,31].…”
Section: Discussionsupporting
confidence: 92%
“…The trophic niche of S. italicus was only studied in subterranean populations [ 12 ]. Researchers have observed high variability in the consumed prey among populations, with a clear predominance of Diptera, one of the most abundant prey in subterranean environments [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Crane flies constitute the majority of prey for various wildlife, including snails, salamanders, and other Arthropoda (Lunghi et al, 2020), in addition to the species observed here (Table 4). A recent study found that crane fly abundance was a key predictor of the persistence of multiple sympatric bird species, and explained 39% of observed bird abundance (Carroll et al, 2015).…”
Section: Conservation Implicationsmentioning
confidence: 75%